ANALISA HUKUM PERALIHAN HAK TANAH ULAYAT KAUM YANG BELUM DIDAFTARKAN DI KABUPATEN DHARMASRAYA - Ratih Agustin Wulandari; Muhammad Sukron; Raimon Efendi (JCH (Jurnal Cendekia Hukum), 2020)
Ulayat land has a social function passed down from ancestors. Tanah Ulayat is a customary community right that cannot be transferred to outsiders, in the Minangkabau kinship system, it is only used for 4 things: gadang girly house, dead body lying in the middle of the house, unmarried girls, upholding the heirloom title. However, at the moment there are a lot of transfers of customary land rights, both sale and purchase. The research uses an empirical juridical approach. The data used are primary data obtained by interview and secondary data obtained through literature study. The results of research into the existence of the transfer of rights to customary land that have not been registered are increasingly high, namely in the form of buying and selling, which has an impact on the social function of customary land has been lost. The practice of buying and selling communal land for people in Koto Baru in the Dharmasraya Regency consists of buying and selling a plot of land and buying and selling a plot of land followed by a customary land grant. Collective Rights on customary land will change to individual rights if there is a transfer of rights to the communal land. This will result in ulayat land which will become private / individual land that will automatically cause harm to the people themselves. Customary philosophical values will fade both high pusako property and low pusako property. And no longer subject to the provisions of customary law.